PELATIHAN BACA PUISI DENGAN GESTUR UNTUK TINGKATKAN PERKEMBANGAN KETERAMPILAN MOTORIKDAN KEBUGARAN JASMANI - Lukman Alfaris; Jamaludin Yusuf, Idah Tresnowati, Mega Widya Putri, Syafig Trisna Syafwana, Rizky Azriel Albani (JOURNAL OF COMMUNITY DEDICATION, 2022)
There are lots of poetry reading lessons when reading many students who do not know poetry reading techniques so that when reading it gives the impression that the intonation is the same in the sense of lilting when it is read. Even though each poem has a different meaning. Lack of expression will reduce the beauty of poetry reading. Therefore, usually before the poem is read, the student must understand the poem. In the poetry reading stage, there are stages starting from knowing the meaning of diction, lines and stanzas. . In learning Indonesian there are several competencies such as speaking competence. Students are taught how to speak in public, read poetry and speeches. One of the speaking competences is vocals, intonation, pauses, articulation and expression. Reading poetry is not like reading speech texts. Poetry also needs gestures in conveying the contents of poetry and gestures are very influential in the communication process. If they are in harmony with verbal language, they will strengthen a more expressive communication process. Gesture is closely related to the appearance of physical behavior for reading poetry. However, gestures cannot completely replace verbal language. While some people use gestures in addition to clarifying verbal language. Systematic processes besides the aesthetics of performing forms, gestures also affect the body, because movements aim to improve or maintain the quality of body functions which include the quality of lung- cardiac endurance, muscle strength, flexibility and body composition during gesture activity.